Proposta de zoneamento ecológico econômico para a área de proteção ambiental (APA) estadual de Tambaba - Paraíba - Almeida, Nadjacleia Vilar (2006)
This work is a proposal of an ecological and economical zoning (ZEE Zoneamento Ecológico Econômico, in Portuguese) for the Environmental Protection Area (APA Área de Proteção Ambiental, in Portuguese) (both categories used by IBAMA, the Brazilian Institute for the Environment and Natural Resources) at Tambaba on the littoral of Paraíba state. The APA of Tambaba is located in the Microregion of the Paraiban southern littoral, in the Mesoregion known as Mata Paraibana (Paraiban woods), in the municipalities of Conde, Pitimbu, and Alhandra. The area is delimited by the watersheds of the stream Caboclo and of the rivers Bucatu, Graú, and Mucatu, which form a drainage basin covering a total area of 114.46 km2. The present ZEE was generated by a model where it is considered the interdependence among the components and phenomena of the geographical space, where several aspects are Tambaba APA s territory is divided into two large zones: the Preservation and the Restoration zones integrated and analysed. In this context, it is necessary to employ technologies that make possible to handle a large amount of data, organized in a way that different interactions may be performed by a combination of social and physical attributes of local environment. The methodology consists on assigning weighted values to evaluate the Human, Productive, Institutional, and Natural Potential aiming the estimation of the social potential of the municipalities that make part of the APA. It was also evaluated local vulnerability with respect to themes related to Geology, Geomorphology (sloping surfaces), Pedology, Climate, and Vegetation/current use of soil according to the ecodynamics theory. Then, the vulnerability values assigned to each theme were integrated by using mathematical formulation which generates a map of vulnerability of the physical environment by employing techniques from geocoding process. In order to obtain a synthesized map of the ZEE, the maps related to the social potentiality and physical vulnerability are integrated, resulting in five use zones, namely: Expansion, Consolidation, Preservation, Restoration, and Institutional Use. This methodology generated the following results: the expansion areas are characterized by low potentiality and low vulnerability (stable) and correspond to top areas totalling 2.32 km2 (2.02% of the APA s area), being more easily found on top sites on the right bank of the Graú River separating the drainage basins of the rivers Graú and Mucatu; the consolidation areas are characterized by high potentiality and low vulnerability (stable), which corresponds to top areas totalling 6.57 km2 (5.74% of the APA s area), being more evident in the BTUs basic territorial units (UTB Unidade Territorial Básica, in Portuguese) at the plain tops that separate the watersheds of the rivers Graú and Bucatu and of the stream Caboclo; the preservation areas presented the highest degree of vulnerability and low potentiality, covering a total area of 32.11 km2, being located in the BTUs to southern of the Tambaba s APA on the right bank of the low and middle course of the Graú River and in the whole hydrologic basin of the Mucatu River, contiguous to the expansion areas; the restoration areas with high vulnerability cover 46.32 km2 and are located north- and westward of the APA, contiguous to the consolidation areas; and finally, the areas related to Institutional use are those protected by the Federal government s, Paraíba state s and municipality s legislations, which represent 23.71% (27.14 km2) of the whole area of the Tambaba s APA. It is noteworthy the urgent need for an effective control of activities carried out in the APA s territory, since the median social potentiality and stability and the moderate instability of the physical environment presented throughout the majority of its territory, propitiate a critical situation, as the